Ejecución de una auditoría operacional al sistema de control interno de los costos de construcción y su incidencia con la gestión administrativa, de la empresa constructora Meylin S.A. del Cantón Quevedo, año 2011 - Sarabia Zambrano, Linda Elizabeth (2012)
The present project of investigation is about the Execution of an Operational Auditing to Internal Control's System of Costs of the construction and its incidence in the Constructora Meylin S.A’s administrative management, year 2011. The theme of the project was elected on the basis of the need that the company of an evaluation had to its present Internal Control, by means of an operational auditing, and according to the results taking measures that they favor to safeguard and the company's resourceful optimization. In accordance with the results of auditing, they detected findings; then they contributed to the administration for each case concrete recommendations, besides the specific proposal is defined, same that contains alternatives of control like; documents of register and back, procedure flowcharts, specification functions of administrative and operational human talent, organizational structure and description of safety clothing for the workers. The project contains the introduction, justification, hoped-for changes, objective, hypothesis, theoretic mark, the results from investigation detailing the process of action of the auditing with your respective documents of support of the present internal control, and the proposal to establish a new procedure of control for the operations related with Internal Control's system of costs of the construction of the company.